The Impact of Corporate Governance on Earnings Management: Empirical Evidence from Listed Companies in Hong Kong - Zhang, Zecheng (2019)
This paper studies the relationship between corporate governance structure and earnings management of listed companies in Hong Kong. The governance structure information and financial data of 911 companies in Hong Kong Stock Exchange made up the sample data of this paper. The duration of sample was a period of three years from 2014 to 2016. The modified Jones model was applied to measure the levels of discretionary accruals, and then the absolute value of discretionary accruals was utilized to represent the levels of earnings management. This paper concentrates on the impact of seven corporate governance factors on earnings management by regression of three panel data models. Then this paper found that four corporate governance factors are significantly correlated with the levels of earnings management. The board independence, the audit committee size and the frequency of audit committee meetings were found to have a significant negative relationship with earnings management, while the meetings frequency of the board of directors displayed a significant positive correlation with earnings management. The main contribution of this paper is to supplement the knowledge body about the impacts of corporate governance on earnings management of listed companies in Hong Kong, as well as several practical implications.